System of Scientific and Technological Support for Hop Growing at the Regional Level - Maria L. TOLSTOVA; Alexandra E. KORNILOVA (Communications of International Proceedings, 2025)
In modern conditions, the domestic brewing industry largely depends on imported supplies of pelleted hops and extracts. Current volumes of hop production in the country reveal only a small share of the processing enterprise. In the context of sanctions pressure on the Russian Federation from unfriendly risk countries, a reduction in hop imports ensures favorable development of the brewing industry. The competitive position of the Russian Federation in the world market of hops and hop products depends mainly on the effectiveness of the policy and the use of reserves for increasing the volume of hop production in the country and improving its quality. This article proposes a classification of the main problems associated with the breakthrough development of the industry, ensuring purity and rapid step-by-step movement, engineering and technological support for the industry, as well as modern and personnel support for the intensification of industry processes. An important development of hop growing is the national project "Technological Support of Food Security", recommended for launch in 2025. The development of selection and specialized mechanical engineering for the hop industry can be considered as the flagship areas of the national project implementation. All the problematic characteristics under consideration take into account the totality of challenges for the resource and technological sovereignty of the country. In this regard, the authors proposed scenario options for the development of events for each direction of hop growing intensification. The most rational seems to be the localization of all stages of hop production and processing in the Russian Federation, which allows ensuring the resource and technological sovereignty of the industry, and accordingly reducing the import dependence of domestic hop growing. An important circumstance indicating the development opportunities is the first experience of domestic brewing companies directly participating in bread production and investing in industries. Some features of the industry development are studied using the example of the lower regions of the Russian Federation, such as the Chuvash Republic and the Krasnodar Territory.Of particular importance for ensuring the intensification of hop growing is state support for promising projects in the industry. Consolidation of federal and regional forms of support allows co-financing not only all the main technologies of hop production, but also the acquisition of domestic planting material and specialized equipment.
Keywords: hop growing; import substitution; selection; personnel; technologies; intensification.